Pedagogy for Effective Learning of Clinical Skills: An Integrated Laboratory Model. Issue 3 (18th September 2020) - Reilly, Michelle; Beran-Shepler, Kimberly; Paschal, Karen A.
Abstract : Background and Purpose: The teaching, learning, and assessment of clinical skills is a critical component of entry-level physical therapy education. The intention of this article was to describe a successful model for teaching clinical skills in the context of the patient and client management model across the domains of physical therapist education with emphasis on motor learning principles, experiential learning, and clinical reasoning. Method/Model Description and Evaluation: The model describes a cohesive laboratory learning environment that integrates skills from the clinical science courses that coincide each semester. A laboratory director coordinates with faculty teaching clinical sciences in a given semester to ensure the necessary psychomotor content is included, creates experiential learning opportunities that integrate skills across content areas, and promotes clinical reasoning in the context of the patient and client management model. Success of this model was measured through student outcomes on skills competency tests (SCTs), Clinical Competence Performance Examinations (CCPEs), American Physical Therapy Association (APTA) Clinical Performance Instrument (CPI) benchmarks, and the National Physical Therapy Examination (NPTE). Outcomes: Each student passed SCTs administered during semesters 1–6 given a maximum of 3 trials. Every student passed the CCPE administered at the end of each semester in one of 3 trials except for one student in semester 6. Each student met expectations for performance as measured on the CPI for 4 clinical education experiences including entry-level performance for the final 2terminal experiences. All students were successful on the NPTE. Discussion and Conclusion: Implementation of this model has prepared students for authentic physical therapy practice by promoting integration of curriculum content and has fostered faculty collaboration. While initial student and curricular outcomes have been positive, assessment of the model is ongoing.